ANALISIS PERLAKUAN AKUNTANSI ATAS PERSEDIAAN BARANG JADI SESUAI DENGAN PSAK NO.14 PADA PT.FORTUNA INTI ALAM - Karundeng, Angellica; Saerang, David; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
So that researchers are encouraged to conduct research whether the accounting treatment of methods of recording, assessment, measurement and disclosure of finished goods inventory at PT. Fortuna Inti Alam has complied with PSAK No.14. This research uses qualitative approach, The types of data collected are primary and secondary data. This study concludes that the accounting treatment of the method of recording, valuation, and measurement of finished goods inventory in PT. Fotuna Inti Alam is in accordance with PSAK No.14 but there are errors in the disclosure of inventory at PT. Fortuna Inti Alam because the company only discloses finished goods inventory in its balance sheet.Keywords : Accounting Treatment, Finished Goods Inventory, PSAK No.14